Studi kelayakan proses pembubutan penekan kopling sepeda motor dengan mesin boxford cnc menggunakan pendekatan statistical process control - Yudhyadi, I GNK.; Wijana, M.; Yasa, I Ketut Sedana; Sayoga, I Made Adi (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2017)
Now days, a company has been experiencing and facing a tight competitive siege. To be surviving within this competition, the company must be creative in developing new and robust ideas to improve their business competitiveness which differentiate them from the others. The product quality was the main issues among others. The quality of a product that offered to the consumers must be cheap and have met with consumer satisfaction. Exploring these ideas, current research has conducted with the main goal was investigating the quality of product produced on CNC Turning. The quality was calculated with a Statistical Process Control (SPC) analysis. Meanwhile, ductile iron workpieces size of 130 mm in length and 19 mm in diameter were manufactured for the samples. The data gathered including diameter, length, and thickness of the samples measured with Digital Vernier Caliper and Micrometer. Based on data observed, the result of experiment shows that the quality of sample products produced in single run (12 products) has met with basic standard requirement with which all samples dimension was lay inside the control limit (Upper and Lower Control Limit (UCL and LCL). It can be concluded that each variable still in process control and was ready for the automation.